Biodiversity of Aquatic Insects of Zayandeh Roud River and Its Branches, Isfahan Province, Iran. - Mansoreh Shayeghi; Hassan Vatandoost; Abdollah Gorouhi; Ali Reza Sanei-Dehkordi; Yaser Salim-Abadi; Mohsen Karami; Mohammad Reza Jalil-Navaz; Amir Ahmad Akhavan; Zahra Shiekh; Sajad Vatandoost; Mohammad Hossein Arandian (Tehran University of Medical Sciences, 2014)
Background: Aquatic insects are the  major groups of arthropods that spend  some parts of their life cycle in the water. These insects play an important role for transmission of some human and animal diseases. There is few information about the aquatic insects fauna of Iran. Methods: To study the aquatic insects fauna, adult, nymphal and larval collections were carried out from different habitats using the standard technique in Zayandeh Roud River, Isfahan Province,central Iran, during summer 2011. Results: In total, 741 speimens of aquatic insects were collected and morphologically identified. They include 7 families and 12 genera representing 2 Orders. The order of  Diptera (92.31%) and Coleoptera (7.69%). The families Culicidae, Syrphidae and Chironomidae from Diptera order, Gyrinidae, Dytiscidae, Haliplidae, Hydrophilidae from Coleoptera order were identified. Conclusion: Some aquatic insects play an important role for transmission of human and animal diseases. These insects also are important for biological control. Therefore ecological study on aquatic insects can provide information about ecology of insects in an area for any decision making.